THE GENERATIVE AI DISRUPTION: A BIBLIOMETRIC ANALYSIS of ARTIFICIAL INTELLEGENCE TRANSFORMATIVE IMPACT ON HOSPITALITY RESEARCH AND PRACTICE - Audio Valentino Himawan Marhendra (Journal of Innovation Research and Knowledge, 2025)
This study provides a comprehensive bibliometric analysis of Artificial Intelligence's transformative impact on hospitality research. Utilizing 3,993 documents from the Scopus database (2011-2025), we map the field's intellectual structure and evolution. Findings reveal exponential publication growth since 2017 and a structure defined by foundational "Basic Themes" (e.g., machine learning) and peripheral "Niche Themes" (e.g., human studies). Critically, the analysis reveals a conspicuous absence of "Motor Themes," indicating the field, while vibrant, lacks a mature, driving research agenda. This paper charts the field's evolution and proposes a data-driven agenda for future inquiry.